2016
DOI: 10.11604/pamj.2016.23.207.8083
|View full text |Cite
|
Sign up to set email alerts
|

An examination of inpatient medical record keeping in the Orthopaedic Department of Kilimanjaro Christian Medical Centre (KCMC), Moshi, Tanzania

Abstract: IntroductionThere is a lack of published evidence examining the quality of patient notes in African healthcare settings. We aim to examine the completeness of the orthopaedic inpatient notes and begin development of a formal audit framework in a large Tanzanian Hospital.MethodsA retrospective review of 155 orthopaedic inpatient notes at Kilimanjaro Christian Medical Centre (KCMC) was conducted spanning 3 months. Notes were reviewed using an agreed data collection pro forma considering 3 main outcomes; i) quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Research studies on information systems specific to SOA were scant. An audit conducted in Kilimanjaro Christian Medical Centre found that patient records were often only partially completed with sections like procedures and follow-up completed 27% and 0% of the time, respectively [28]. A review of government policies and databases revealed that a limited number of surgical data are currently being collected at the national level [24].…”
Section: Information Managementmentioning
confidence: 99%
“…Research studies on information systems specific to SOA were scant. An audit conducted in Kilimanjaro Christian Medical Centre found that patient records were often only partially completed with sections like procedures and follow-up completed 27% and 0% of the time, respectively [28]. A review of government policies and databases revealed that a limited number of surgical data are currently being collected at the national level [24].…”
Section: Information Managementmentioning
confidence: 99%
“…In Poland, the reported POMR of 1% revealed notable 18% discrepancies, 29 highlighting challenges even in high‐resource settings. Fifteen Tanzanian studies on surgical data management revealed severe lacks, aligning with studies showing incomplete patient information; sections such as procedures and follow‐up were completed only 27% and 0% of the time, respectively 30 …”
Section: Discussionmentioning
confidence: 99%
“…Fifteen Tanzanian studies on surgical data management revealed severe lacks, aligning with studies showing incomplete patient information; sections such as procedures and follow-up were completed only 27% and 0% of the time, respectively. 30 Tanzanian NSOAPs prioritize enhancing information management systems. 2,13 MOI stakeholders endorsed the platform for improving data management, which addressed existing repository challenges.…”
Section: World Journal Of Surgerymentioning
confidence: 99%
“…In order for Africa not be left behind in all these highly beneficial technologies, innovation and maximization of the existing infrastructure is highly required. A sine qua non to research and innovative discoveries is good record keeping; which remains sub-optimally practiced in most developing economies [ 5 9 ]. For example, it has been historically recorded that two previous presidents of the United States of America (Ulysses Simpson Grant & Stephen Grover Cleveland) were diagnosed with oral cancer [ 10 , 11 ]; however such information is lacking on how many African presidents have had oral cancer in the past.…”
Section: Introductionmentioning
confidence: 99%